Influence of process conditions on measles virus stability - Weiss, K.; Salzig, D.; Röder, Y.; Gerstenberger, J.; Mühlebach, M. D.; Cichutek, K.; Pörtner, R.; Czermak, Peter (My University, 2013)
Recombinant measles viruses are currently tested in clinical trials as oncolytic agent to be applied in cancer therapy. Contrary to their use as vaccine where 10³ infectious virus particles per dose are needed, for cancer therapy 10[superscript 9] virus particles should be provided per dose. This leads to other challenges for the production process when compared to vaccine production. This study presents measles virus stability with regard to conditions during production and storage of the virus. Relevant process parameters such as temperature (4-37°C), pH (pH 4-11), conductivity (1.5 to 137.5 mS cmˉ¹) and oxygen partial pressure were analyzed. The infectivity of measles virus particles decreased highly at 37 and 32°C, while at 22 and 4°C it remained stable for several hours or even days, respectively. The thermal inactivation reactions followed first order kinetics and the thermodynamic parameters enthalpy and entropy were estimated. Towards changes in pH measles virus particles were very sensitive, while no inactivation could be observed with varying conductivity. Measles virus incubation at an oxygen partial pressure of 100% did not lead to any loss of infectivity. The results show which parameters should be considered and controlled strongly in the production process to further raise measles virus yields for the high amount needed in cancer therapy approaches.
Keywords: Measles virus; Virus stability; Virus inactivation; Oncolytic agent